2021
DOI: 10.1007/s10554-021-02421-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of electrocardiography, echocardiography and cardiac T2* for cardiac complications in beta thalassemia major

Abstract: Cardiac complications such as heart failure and arrhythmias caused by "iron-induced" cardiomyopathy are considered as the primary cause of death in the patients with β-thalassemia major. The aim of this study was to evaluate electrocardiography, echocardiography according cardiac T2* and ferritin ndings of patients followed-up for β-thalassemia major, and to investigate the importance of these ndings for early detection of cardiac complications. The study included 41 patients and 25 healthy individuals with ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Fiftyseven percent of instances showed myocardial dysfunction, and 27% displayed ECG abnormalities, including arrhythmias. However, Ersoy Dursun et al (30) Ethical Approval: This study was approved by the ethical committee, faculty of medicine, all methods were performed in accordance with the relevant guidelines and regulations. Approval code number 315:4/2022.…”
Section: Resultsmentioning
confidence: 99%
“…Fiftyseven percent of instances showed myocardial dysfunction, and 27% displayed ECG abnormalities, including arrhythmias. However, Ersoy Dursun et al (30) Ethical Approval: This study was approved by the ethical committee, faculty of medicine, all methods were performed in accordance with the relevant guidelines and regulations. Approval code number 315:4/2022.…”
Section: Resultsmentioning
confidence: 99%
“…This was in concordance with the result from Fadime et al, 2022 who studied 41 patients with beta-thalassemia major and 25 healthy control evaluate electrocardiography, echocardiography according cardiac T2* and ferritin findings of patients followed-up for β-thalassemia major, and to investigate the importance of these findings for early detection of cardiac complications and found that no significant difference regarding to EF, LVESV and LVESDV between 2 groups. [11] Compared with controls, the diastolic indices of LV in beta thalassemia major patients showed significantly higher E wave velocity which confirmed by Ragab et al, 2015 who studied 25 patients with beta-thalassemia major and 20 healthy controls to investigate non-overt cardiac dysfunctions in beta thalassemia major patients using pulsed wave Tissue Doppler Imaging (TD I) and its relation to iron overload and brain natriuretic peptide and found that significant increase of E wave velocity in additional to non-significant difference of A wave velocity and E/A ratio in beta thalassemia major patient comparing with health control group [12]. Similar results to these findings were recorded by Chanpura et al, 2019 this study included 35 patients with beta-thalassemia major and 35 healthy to document echocardiographic changes of cardiac iron overload in patients of thalassemia major even before appearance of symptoms and found that E wave velocity was significantly high in beta thalassemia major patient comparing with health control group [13] .The study also found that A wave velocity and E/A ratio were significantly high in beta thalassemia major patient comparing with health control group.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Dursun et al, the authors found that lower cardiac T2* MRI conduction time was associated with a larger interventricular septum and higher left ventricular mass, which can be due to iron deposition in the cardiac tissue [ 18 ]. However, no association was found between T2* MRI conduction time and left ventricular ejection fraction.…”
Section: Discussionmentioning
confidence: 99%